PENGARUH SELF EFFICACY DAN KOMPETENSI PROFESIONAL TERHADAP MOTIVASI BERPRESTASI DENGAN MEDIASI KEPUASAN KERJA - Tarmidi, 12.5202.0109; Fauzan, Moh. (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimstoanalyzethe influenceInfluenceof WorkMotivationandDisciplineSupervisiononTeacher PerformanceModeratedElementaryPrincipal atSe-District of BatangBatang. Inthis studypopulation ofallprimary schoolteachersin the District ofBatangPNS, whereasthe sample usedwas 131persons asrespondentsto thecensustechnique. WitharespondentcriteriaPNSElementaryTeachersinthe DistrictEducation OfficeTrunkUnit.Measurementsusinga Likert scaleof 7 (seven) alternative answers. Testinstrumentsused arevalidity and reliability. While thetestmodel usedisthe coefficientof determinationandF test(goodnes of Fit). Testthis hypothesisusingregressionanalysis. Based onthe results ofthe studycan be summarized asfollows: (i) Motivationandpositive and significant impactonteacher performance, (ii) Work Disciplinehas no effect onteacher performance, (iii) SupervisingPrincipaldoes notmoderate theeffect ofmotivationonteacher performance, and(iv) PrincipalsupervisionWork Disciplinedoes notmoderate theinfluenceof theTeacher Performance. Keywords: Work Motivation, Work Discipline, SupervisingPrincipal, andTeacherPerformance